Risk of Miscarriage Following Amniocentesis or Chorionic Villus Sampling: Systematic Review of Literature and Updated Meta-analysis. Issue 3 (March 2020) - Salomon, L. J.; Sotiriadis, A.; Wulff, C. B.; Odibo, A.; Akolekar, R.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2019;54:442–451) Evidence suggests that the risk of miscarriage after invasive prenatal testing is much lower than that cited by professional bodies. Since the last reported systematic review of this risk in 2015, more large studies have been conducted, and advances in equipment and techniques have been made.